The Effect of Antibiotics on the Infant Gut Fungal Microbiota - Ventin-Holmberg Rebecka; Saqib Schahzad; Korpela Katri; Nikkonen Anne; Peltola Ville; Salonen Anne; de Vos Willem M.; Kolho Kaija-Leena (MDPI, 2022)
Antibiotics are commonly used drugs in infants, causing disruptions in the developing gut microbiota with possible detrimental long-term effects such as chronic inflammatory diseases. The focus has been on bacteria, but research shows that fungi might have an important role as well. There are only a few studies on the infant gut fungal microbiota, the mycobiota, in relation to antibiotic treatment. Here, the aim was to investigate the impact of antibiotics on the infant gut mycobiota, and the interkingdom associations between bacteria and fungi. We had 37 antibiotic-naive patients suffering from respiratory syncytial virus, of which 21 received one to four courses of antibiotics due to complications, and 16 remained antibiotic-naive throughout the study. Fecal samples were collected before, during and after antibiotic treatment with a follow-up period of up to 9.5 months. The gut mycobiota was studied by Illumina MiSeq sequencing of the ITS1 region. We found that antibiotic use affected the gut mycobiota, most prominently seen as a higher relative abundance of Candida (p < 0.001), and a higher fungal diversity (p = 0.005-0.04) and richness (p = 0.03) in the antibiotic-treated infants compared to the antibiotic-naive ones at multiple timepoints. This indicates that the gut mycobiota could contribute to the long-term consequences of antibiotic treatments.